Altered glycan accessibility on native immunoglobulin G complexes in early rheumatoid arthritis and its changes during therapy - Stuemer, J.; Biermann, Mona; Knopf, Jasmin; Magorivska, I.; Kastbom, A.; Svaerd, A.; Janko, Christina; Bilyy, R.; Schett, Georg; Sjoewall, C.; Herrmann, Martin; Munoz, Luis Enrique; et al. (Clinical and Experimental Immunology, 2017)
The goal of this study was to investigate the glycosylation profile of native immunoglobulin (Ig)G present in serum immune complexes in patients with rheumatoid arthritis (RA). To accomplish this, lectin binding assays, detecting the accessibility of glycans present on IgG-containing immune complexes by biotinylated lectins, were employed. Lectins capturing fucosyl residues (AAL), fucosylated tri-mannose N-glycan core sites (LCA), terminal sialic acid residues (SNA) and O-glycosidically linked galactose/N-acetylgalactosamine (GalNac-L) were used. Patients with recent-onset RA at baseline and after 3-year follow-up were investigated. We found that native IgG was complexed significantly more often with IgM, C1q, C3c and C-reactive protein (CRP) in RA patients, suggesting alterations of the native structure of IgG. The total accessibility of fucose residues on captured immune complexes to the respective lectin was significantly higher in patients with RA. Moreover, fucose accessibility on IgG-containing immune complexes correlated positively with the levels of antibodies to cyclic citrullinated peptides (anti-CCP). We also observed a significantly higher accessibility to sialic acid residues and galactose/GalNAc glyco-epitopes in native complexed IgG of patients with RA at baseline. While sialic acid accessibility increased during treatment, the accessibility of galactose/GalNAc decreased. Hence, successful treatment of RA was associated with an increase in the SNA/GalNAc-L ratio. Interestingly, the SNA/GalNAc-L ratio in particular rises after glucocorticoid treatment. In summary, this study shows the exposure of glycans in native complexed IgG of patients with early RA, revealing particular glycosylation patterns and its changes following pharmaceutical treatment.
EVALuna2:13418

Autoantibodies Recognizing Secondary NEcrotic Cells Promote Neutrophilic Phagocytosis and Identify Patients With Systemic Lupus Erythematosus - Biermann, Mona; Boeltz, Sebastian; Pieterse, Elmar; Knopf, Jasmin; Rech, Jürgen; Bilyy, Rostyslav; Van Der Vlag, Johan; Tincani, Angela; Distler, Jörg; Krönke, Gerhard; Schett, Georg; Herrmann, Martin; et al. (Frontiers in Immunology, 2018)
Deficient clearance of apoptotic cells reportedly contributes to the etiopathogenesis of the autoimmune disease systemic lupus erythematosus (SLE). Based on this knowledge, we developed a highly specific and sensitive test for the detection of SLE autoantibodies (AAb) utilizing secondary NEcrotic cell (SNEC)-derived material as a substrate. The goal of the present study was to validate the use of SNEC as an appropriate antigen for the diagnosis of SLE in large cohort of patients. We confirmed the presence of apoptotically modified autoantigens on SNEC (dsDNA, high mobility group box 1 protein, apoptosis-associated chromatin modifications, e.g., histones H3-K27-me3; H2A/H4 AcK8,12,16; and H2B-AcK12). Anti-SNEC AAb were measured in the serum of 155 patients with SLE, 89 normal healthy donors (NHD), and 169 patients with other autoimmune connective tissue diseases employing SNEC-based indirect enzyme-linked immunosorbent assay (SNEC ELISA). We compared the test performance of SNEC ELISA with the routine diagnostic tests dsDNA Farr radioimmunoassay (RIA) and nucleosome-based ELISA (anti-dsDNA-NcX-ELISA). SNEC ELISA distinguished patients with SLE with a specificity of 98.9% and a sensitivity of 70.6% from NHD clearly surpassing RIA and anti-dsDNA-NcX-ELISA. In contrast to the other tests, SNEC ELISA significantly discriminated patients with SLE from patients with rheumatoid arthritis, primary anti-phospholipid syndrome, spondyloarthropathy, psoriatic arthritis, and systemic sclerosis. A positive test result in SNEC ELISA significantly correlated with serological variables and reflected the uptake of opsonized SNEC by neutrophils. This stresses the relevance of SNECs in the pathogenesis of SLE. We conclude that SNEC ELISA allows for the sensitive detection of pathologically relevant AAb, enabling its diagnostic usage. A positive SNEC test reflects the opsonization of cell remnants by AAb, the neutrophil recruitment to tissues, and the enhancement of local and systemic inflammatory responses.
EVALuna2:34144

Blood-borne phagocytes internalize urate microaggregates and prevent intravascular NETosis by urate crystals - Pieterse, Elmar; Jeremic, Ivica; Czegley, Christine; Weidner, Daniela; Biermann, Mona; Veissi, Susan; Maueröder, Christian; Schauer, Christine; Bilyy, Rostyslav; Dumych, Tetiana; Hoffmann, Markus; Munoz, Luis Enrique; et al. (Scientific Reports, 2016)
Hyperuricemia is strongly linked to cardiovascular complications including atherosclerosis and thrombosis. In individuals with hyperuricemia, needle-shaped monosodium urate crystals (nsMSU) frequently form within joints or urine, giving rise to gouty arthritis or renal calculi, respectively. These nsMSU are potent instigators of neutrophil extracellular trap (NET) formation. Little is known on the mechanism(s) that prevent nsMSU formation within hyperuricemic blood, which would potentially cause detrimental consequences for the host. Here, we report that complement proteins and fetuins facilitate the continuous clearance by blood-borne phagocytes and resident macrophages of small urate microaggregates (UMA; <1 ?m in size) that initially form in hyperuricemic blood. If this clearance fails, UMA exhibit bipolar growth to form typical full-sized nsMSU with a size up to 100 ?m. In contrast to UMA, nsMSU stimulated neutrophils to release NETs. Under conditions of flow, nsMSU and NETs formed densely packed DNase I-resistant tophus-like structures with a high obstructive potential, highlighting the importance of an adequate and rapid removal of UMA from the circulation. Under pathological conditions, intravascularly formed nsMSU may hold the key to the incompletely understood association between NET-driven cardiovascular disease and hyperuricemia.
EVALuna2:13377

Experimental lupus is aggravated in mouse strains with impaired induction of neutrophil extracellular traps - Kienhofer, Deborah; Hahn, Jonas; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Urbonaviciute, Vilma; Johnsson, Caroline; Maueröder, Christian; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; Harrer, Thomas; et al. (JCI Insight, 2017)
Many effector mechanisms of neutrophils have been implicated in the pathogenesis of systemic lupus erythematosus (SLE). Neutrophil extracellular traps (NETs) have been assigned a particularly detrimental role. Here we investigated the functional impact of neutrophils and NETs on a mouse model of lupus triggered by intraperitoneal injection of the cell death-inducing alkane pristane. Pristane-induced lupus (PIL) was aggravated in 2 mouse strains with impaired induction of NET formation, i.e., NOX2-deficient (Ncf1-mutated) and peptidyl arginine deiminase 4-deficient (PAD4-deficient) mice, as seen from elevated levels of antinuclear autoantibodies (ANAs) and exacerbated glomerulonephritis. We observed a dramatically reduced ability to form pristane-induced NETs in vivo in both Ncf1-mutated and PAD4-deficient mice, accompanied by higher levels of inflammatory mediators in the peritoneum. Similarly, neutropenic Mcl-1ΔMyelo mice exhibited higher levels of ANAs, which indicates a regulatory function in lupus of NETs and neutrophils. Blood neutrophils from Ncf1-mutated and human individuals with SLE exhibited exuberant spontaneous NET formation. Treatment with specific chemical NOX2 activators induced NET formation and ameliorated PIL. Our findings suggest that aberrant NET is one of the factors promoting experimental lupus-like autoimmunity by uncontrolled release of inflammatory mediators.
EVALuna2:1833

Externalized decondensed neutrophil chromatin occludes pancreatic ducts and drives pancreatitis - Leppkes, Moritz; Maueröder, Christian; Hirth, Sebastian; Nowecki, Stefanie; Günther, Claudia; Billmeier, Ulrike; Paulus, Susanne; Biermann, Mona; Munoz, Luis Enrique; Hoffmann, Markus; Wildner, Dane; Croxford, Andrew L.; et al. (Nature Communications, 2016)
Ductal occlusion has been postulated to precipitate focal pancreatic inflammation, while the nature of the primary occluding agents has remained elusive. Neutrophils make use of histone citrullination by peptidyl arginine deiminase-4 (PADI4) in contact to particulate agents to extrude decondensed chromatin as neutrophil extracellular traps (NETs). In high cellular density, NETs form macroscopically visible aggregates. Here we show that such aggregates form inside pancreatic ducts in humans and mice occluding pancreatic ducts and thereby driving pancreatic inflammation. Experimental models indicate that PADI4 is critical for intraductal aggregate formation and that PADI4-deficiency abrogates disease progression. Mechanistically, we identify the pancreatic juice as a strong instigator of neutrophil chromatin extrusion. Characteristic single components of pancreatic juice, such as bicarbonate ions and calcium carbonate crystals, induce aggregated NET formation. Ductal occlusion by aggregated NETs emerges as a pathomechanism with relevance in a plethora of inflammatory conditions involving secretory ducts.
EVALuna2:2052

Low amounts of bisecting glycans characterize cerebrospinal fluid-borne IgG - Knopf, Jasmin; Magorivska, Iryna; Maier, Jan-Niklas; Spitzer, Philipp; Bilyy, Rostyslav; Biermann, Mona; Hychka, Kateryna; Bondt, Albert; Wuhrer, Manfred; Toes, Rene E. M.; Schett, Georg; Herrmann, Martin; et al. (Journal of Neuroimmunology, 2018)
Immunoglobulin G (IgG) harbors a conserved N-glycosylation site which is important for its effector functions. Changes in glycosylation of IgG occur in many autoimmune diseases but also in physiological conditions. Therefore, the glycosylation pattern of serum IgG is well characterized. However, limited data is available on the glycosylation pattern of IgG in cerebrospinal fluid (CSF) compared to serum. Here, we report significantly reduced levels of bisected glycans in CSF IgG. Galactosylation and sialylation of IgG4 also differed significantly. Therefore, we propose a common mechanism mediating glycosylation changes of IgG at the transition from serum to CSF in steady state conditions.
EVALuna2:34466

ROS is the boss - Hahn, Jonas; Kienhofer, Deborah; Stoof, Julia; Csepregi, Janka Zsofia; Reinwald, Christiane; Maueröder, Christian; Urbonaviciute, Vilma; Munoz, Luis Enrique; Hultqvist, Malin; Podolska, Malgorzata; Biermann, Mona; Leppkes, Moritz; et al. (2017)
EVALuna2:13467

Sweet but dangerous - the role of immunoglobulin G glycosylation in autoimmunity and inflammation - Biermann, Mona; Griffante, G.; Podolska, Malgorzata; Boeltz, Sebastian; Stürmer, Jörg; Munoz, Luis Enrique; Bilyy, R.; Herrmann, Martin; Munoz Becerra, Luis (Lupus, 2016)
Glycosylation is well-known to modulate the functional capabilities of immunoglobulin G (IgG)-mediated cellular and humoral responses. Indeed, highly sialylated and desialylated IgG is endowed with anti- and pro-inflammatory activities, respectively, whereas fully deglycosylated IgG is a rather lame duck, with no effector function besides toxin neutralization. Recently, several studies revealed the impact of different glycosylation patterns on the Fc part and Fab fragment of IgG in several autoimmune diseases, including systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Here, we provide a synoptic update summarizing the most important aspects of antibody glycosylation, and the current progress in this field. We also discuss the therapeutic options generated by the modification of the glycosylation of IgG in a potential treatment for chronic inflammatory diseases.
EVALuna2:13284

The role of dead cell clearance in the etiology and pathogenesis of systemic lupus erythematosus: dendritic cells as potential targets - Biermann, Mona; Veissi, Susan; Maueröder, Christian; Chaurio Gonzalez, Ricardo Alfredo; Berens, Christian; Herrmann, Martin; Munoz Becerra, Luis (Expert Review of Clinical Immunology, 2014)
Overwhelming apoptosis combined with a deficiency in clearing apoptotic cells is thought to be an important etiopathogenic event in the autoimmune disease systemic lupus erythematosus (SLE). Lazy macrophages, complement or DNase I deficiency as well as insufficient natural IgM might be important factors leading to such a clearance deficiency. A defective clearance of apoptotic cells leads to the activation and maturation of plasmacytoid and myeloid dendritic cells (DCs) by material derived from secondary necrotic cells carrying modified autoantigens. This results in the presentation of autoantigens to autoreactive T and B cells in an immunogenic manner, thereby leading to autoantibody production, chronic inflammation and severe tissue damage. Since DC activation and IFN-? production by plasmacytoid dendritic cells play a critical role in the course of SLE pathogenesis, therapeutic intervention to end this vicious cycle might be a promising approach for treating the disease.
EVALuna2:13019